Never ask for a lighter rain but a stronger umbrella - Pande, Saket; Haeffner, Melissa; Blöschl, Günter; Alam, Mohammad Faiz; Castro, Cyndi; Di Baldassarre, Giuliano; FrickTrzebitzky, Fanny; Hogeboom, Rick; Kreibich, Heidi; Mukherjee, Jenia; Mukherji, Aditi; Nardi, Fernando; et al. (Frontiers in water, 2021)
In a recent Nature Sustainability editorial, the editors raised the concern that journal submissions on water studies appear too similar (17 August 2021, Nat Sust 4, 659). The gist of the editorial: “too many publications and not enough ideas”. In this response, we contest this notion, and point out that numerous new ideas are now emerging that result from taking a broader view of the water science field. Drawing inspiration from a recently hosted conference geared at transcending traditional disciplinary silos and forging new paradigms for water research, we are, in fact, enthusiastic and optimistic about the ways scientists are investigating political, economic, historical, and cultural intersections towards more just and sustainable human-water relations and ways of knowing.